Задачі оптимального керування потоками газу в довгому трубопроводі - Чекурін, В. Ф.; Химко, О. М. (НТУ "ХПІ", 2015)
В рамках моделі газової динаміки сформульовані задачі оптимального керування стаціонарними режимами транспортування газу в довгому газопроводі. Запропоновані алгоритми чисельного розв’язування сформульованих задач. Розглянута можливість застосування розробленого математичного апарату для управління магістральними газопроводами.

A section of a gas-main pipeline consisting of a compression station and connected to it output long pipeline has been considered in the paper. Problems for optimal control by steady-state natural gas flows in the section have been formulated within the non-linear gas dynamic model. The solutions of the problems determine the values of the pressure on the pipeline’s input and output under which the power consumption of the compression station is minimal. The problems have been reduced to non-restricted minimization of functionals depending on power of gas frictional forces in the pipeline. An algorithm for numerical solving the formulated problems has been created with the use of Runge-Kutta and Newton methods. The developed mathematical tools can be used for formulation and solving problems for optimalcontrol by steady-state natural gas flows in many-sectional gas-main pipelines.
Problems for optimal control by natural gas flows in a long pipeline
Keywords: газова динаміка; магістральні газопроводи; компресорні станції; транспортування газу; gas dynamics; gas-main pipeline; optimal control